Two new species of the congrid eel genus Ariosoma (Anguilliformes, Congridae, Bathymyrinae) from Indian waters - Paramasivam Kodeeswaran; Ayyathurai Kathirvelpandian; Dipanjan Ray; Anil Mohapatra; Thipramalai Thangappan Ajith Kumar; Chelladurai Raghunathan; Uttam Kumar Sarkar (Zoosystematics and Evolution, 2024)
Two new species have been described from Indian waters, based on the materials collected from Kochi coast, Arabian Sea, Gulf of Mannar and West Bengal coast along the Bay of Bengal. Ariosoma gracile sp. nov. is described, based on five specimens collected from the landings at Kalamukku Fishing Harbour, Arabian Sea. The new species is characterised by longer tail, 55.3–58.7% TL; dorsal-fin origin above pectoral-fin base; no dark or whitish bands on dorsal surface of head, ventral extremities of lower jaw and mid-portion with minute dark pigmentation patch; anus positioned well before the middle of total length; SO canal with 4 pores; 0 or 3 pores on ST canal; pre-dorsal vertebrae 9; pre-anal vertebrae 49–54; total vertebrae 140–142. Ariosoma gracile sp. nov. is closely related to Ariosoma dolichopterum and Ariosoma emmae by sharing similar morphometrics and pre-anal vertebral counts. However, it differs by having more total pores (132–135 vs. 121–129 in A. dolichopterum, 123–126 in A. emmae); fewer pre-anal pores (43–46 vs. 47–51 in A. dolichopterum, 50–53 in A. emmae); more pre-dorsal pores (9 vs. 5–9 in A. dolichopterum, 4–6 in A. emmae). Another new species, Ariosoma kannani sp. nov. is described on the basis of two specimens (157–171 mm TL) from Gulf of Mannar and one specimen (201 mm TL) collected from Shankarpur Fish Landing Centre, West Bengal. This species is similar to Ariosoma megalops, but readily differs by having smaller eyes, smaller interorbital distance and exhibits 10.8% genetic divergence from A. megalops from the Taiwan waters.